MP20: Prevalence of incidental findings on chest computed tomography in patients with suspected pulmonary embolism in the ED. (15th May 2017) - Anjum, O.; Ohle, R.; Bleeker, H.; Perry, J.J.
Abstract : Introduction: Computed tomographic pulmonary angiograms (CTPAs) are often ordered to evaluate pulmonary embolism (PE) in the emergency department (ED). However, these studies often yield alternative diagnoses and report incidental findings that lead to additional unnecessary investigations. Our objective was to assess the prevalence and significance of such findings and their implications in patient management.Methods: This is a retrospective cohort study of adults presenting to two tertiary care EDs in 2015, being evaluated with CTPA for PE. Data was extracted by two reviewers from electronic CT records with inter-rater reliability reported using kappa statistic. We measured prevalence of PE, incidental findings and alternative diagnoses with data reported as mean and standard deviation (SD). Univariate analyses were performed with t-test for continuous variables and Mantel-Haenszel test for categorical variables. A sample size of 770 was calculated based on an expected difference in prevalence between significant and non-significant incidental findings of 80% (α=5%, Power=90%).Results: A total of 1629 studies were included (mean 62 yrs, SD 16.7, 56.9% female, median CTAS score 2, 45.2% admitted). PE was found in 233 (14.3%) patients. 173 (10.6%) studies had a finding of an alternative diagnosis, the majority being pulmonary infiltrates (n=130, 75.1%). In patients who underwent both CTPA and chest x-ray (CXR), CXRs alone would have led to the same alternative diagnosis in 116 (77.1%) patients. A total of 223 (13.6%) patients had an incidental finding; the majority included pulmonary nodules (n=83, 37.2%) and adenopathy (n=26, 11.6%). Only 26 (17.1%) incidental findings were significant; most common included pulmonary nodules (n=6, 3.9%) and masses (n=7, 4.6%) that lead to newly identified and biopsied lung cancer diagnoses. Incidental findings led to an additional 301 follow-up CTs with a yield of significant result of 9.2% (n=48 CTs).Conclusion: Chest CTs ordered in the ED for clinical suspicion of PE is equally as likely to identify alternative diagnoses or incidental findings as PE. The majority of incidental findings are non-significant and result in an increased use of CT. CXRs should routinely be ordered prior to further investigation for PE with chest CT to reduce unnecessary testing and thus time and cost to the system.